Taxation and self-employment - Zsófia L. Bárány (Luxembourg Income Study (LIS), 2017)
In this paper I theoretically show that if the self-employed evade income taxes, then the choice of being self-employed is more sensitive to the tax rates on wages than to tax rates on income from self-employment. Using variation in the statutory tax rates across countries, industries, and occupations, I find evidence that supports the predictions of the model. This suggests that those who choose self-employment, partly do so to take advantage of the technology it offers in evading taxes. This extensive margin of adjustment - between employment and self-employment - should be taken into account when considering the effects of tax rates on labor income, on taxable income and on welfare.
Keywords: 330